PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA ARAB MELALUI APLIKASI VIDEOSCRIBE DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - A. Hasan, Adtman; Baroroh, Umi (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2019)
This paper describes the use of Scribe Video as a Media in Learning Arabic to Improve Student Learning Motivation. The problem of education and teaching is a fairly complex problem where there are many factors that influence it. One of these factors is the teacher. The teacher is a component of teaching that plays an important and primary role, because the success of the learning process is largely determined by the teacher's factor. The teacher's task is to convey the subject matter to students through communication interactions in the learning process that they do. The success of the teacher in delivering the material is very dependent on the smooth interaction between the teacher and the students. This study uses development research methods in education or in English development research, a process in developing and validating educational products. The purpose of this research is to develop Arabic learning media using software sparkol (video scribe) in increasing student learning motivation. This research is a research and development focusing on software sparkol (video scribe). Videoscribe is a software (software) for automatically creating whiteboard animation (whiteboard animation). Videoscribe was launched in 2012 by sparkol company United Kingdom (UK) in the UK. Videoscribe is developed by Adobe Flash and Flash Video. Videoscribe is a form of video media with a blackboard concept that uses hand drawings and as if it were drawing or writing on the board. The concept of videoscribe is usually used as a video presentation, promotion, learning, and so on.